Factores sociales e incumplimiento materno en el control de niño sano, Hospital Belén, Trujillo, 2021 - Rodríguez Villena, Fresia Antonella (2022)
This thesis was carried out with the purpose of analyzing the influence of social factors on maternal noncompliance in the Control of healthy children, Hospital Belén, Trujillo, 2021. The type of applied research has been considered, based on a descriptive design, and the sample consisted of 48 mothers who are in a situation of maternal non-compliance with the Healthy Child Control; with which we worked applying the methods and techniques of quantitative research: Statistical method and as a survey technique, and qualitative research: Inductive - deductive method; and direct observation and interview techniques. In summary, it has been possible to show that there are socioeconomic, cultural and institutional factors in the non-compliance with the control of growth and development of children under one year of age. This thesis is subdivided into: I. Introduction: Problematic reality, background, theoretical bases and conceptual framework; II. Materials and methods; III. Results presentation; IV. Discussion of results. V. Conclusions; SAW. Recommendations. VII. Bibliographic references and Annexes.